2017
DOI: 10.3389/fmicb.2017.00325
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Endophytic Fungal Community Associated with Oryza sativa L. and Zea mays L.

Abstract: In a natural ecosystem, the plant is in a symbiotic relationship with beneficial endophytes contributing huge impact on its host plant. Therefore, exploring beneficial endophytes and understanding its interaction is a prospective area of research. The present work aims to characterize the fungal endophytic communities associated with healthy maize and rice plants and to study the deterministic factors influencing plant growth and biocontrol properties against phytopathogens, viz, Pythium ultimum, Sclerotium or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(87 citation statements)
references
References 66 publications
4
82
0
1
Order By: Relevance
“…The results for L . radiata are consistent with the perspective that the composition of fungal endophytes in different organs of most plants is quite different (Kumar and Hyde, ; Mishra et al ., ; Wearn et al ., ; Clay et al ., ; Potshangbam et al ., ). It has already been explained that some defensive factors in planta , such as plant secondary metabolites, can regulate the colonization and growth of fungal endophytes in different plant organs (Saunders and Kohn, ).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The results for L . radiata are consistent with the perspective that the composition of fungal endophytes in different organs of most plants is quite different (Kumar and Hyde, ; Mishra et al ., ; Wearn et al ., ; Clay et al ., ; Potshangbam et al ., ). It has already been explained that some defensive factors in planta , such as plant secondary metabolites, can regulate the colonization and growth of fungal endophytes in different plant organs (Saunders and Kohn, ).…”
Section: Resultsmentioning
confidence: 97%
“…radiata (Fig. ); similar results have been described in many other plants (Kumar and Hyde, ; Mishra et al ., ; Wearn et al ., ; Clay et al ., ; Potshangbam et al ., ). This may be because the diverse physiological status of different organs leads to different conditions for fungal endophytes (Aly et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Accumulated evidence has confirmed that plant endophytes from special orextreme environment has many effects on host ecological adaptability [3][4][5]. It is well known that the concurrence of endophytes may accelerate plant growth and increase the survival rate of biotic or abioticstresses, such as plant diseases, pests, drought, salinity and extreme temperatures [6][7][8][9]. Specifically, some endophytes are beneficial to plants by producing special substances, such as secondary metabolites, which can prevent the host from being attacked successfully by fungi and pests [10].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence has confirmed that plant endophytes from special or extreme environment has many effects on host ecological adaptability [3][4][5]. It is well known that the concurrence of endophytes may accelerate plant growth and increase the survival rate of biotic or abiotic stresses, such as plant diseases, pests, drought, salinity and extreme temperatures [6][7][8][9]. Specifically, some endophytes are beneficial to plants by producing special substances, such as secondary metabolites, which can prevent the host from being attacked successfully by fungi and pests [10].…”
Section: Introductionmentioning
confidence: 99%